Investigating the effects of STEM enriched implementations on school readiness and concept acquisition of children - (:unkn) unknown (Ankara University, 2020)
The aim of the study is to investigate the effect of STEM enriched preschool education implementations on children's school readiness and concept acquisition. The study was conducted with experimental design with pretest-posttest control group. The sample group of the study consisted of thirty-three children from the age group of 60-68 months. While 16 of the children were included in experimental group, 17 were included in control group. Before the implementations, the activities which were based on STEM skills and for which expert opinions were taken were developed. All activities were completed in nine weeks. Bracken Basic Concept Scale-Revised Form was used as the data collection tool in the pretest-posttest. As a result of the study, it was found that there was a statistically significant difference between the total scores of both school readiness and concept acquisition in favor of the experimental group. Based on the results, it can be asserted that early STEM activities supported preschool education program in school readiness and concept acquisition. © 2020, Ankara University. All rights reserved.
Keywords: Concept acquisition; School readiness; STEM education; STEM in preschool education